Educational expansion, poverty reduction and social mobility: Reframing the debate. (2020) - Brown, Phillip; James, David
Highlights: The expansion of higher education is unlikely to reduce poverty. Policy debates on education and poverty need to focus on the rich as well as the poor. Education as a source of social mobility is extremely limited without expanding job opportunities. Poverty reduction depends on address inequalities of condition as well as inequalities in educational opportunities. The policy debates on education and poverty needs to be reframed. Abstract: This article examines the role of education in alleviating poverty in a context of high rates of income inequalities. It will argue that despite public attention on the incomes of top earners, education policy has been largely silent on the education of elites. Rather it has focused on extending opportunities to those at the other end of the income distribution. By improving school performance and widening access to higher education, it is claimed that poverty can be alleviated by increasing rates of social mobility from disadvantaged families. This article will highlight several problems with this analysis that amount to a fundamental contradiction at the heart of education policy as a route to poverty reduction.